2015
DOI: 10.5021/ad.2015.27.5.492
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessment in Korean Patients with Pemphigus

Abstract: BackgroundMeasuring the quality of life (QOL) is important in the evaluation of nonclinical aspects of diseases, for the discovery of functional and psychological limitations, and in choosing treatment in the initial phase of the disease. Pemphigus is a potentially fatal autoimmune bullous disease caused by autoantibodies against desmogleins (cadherin family proteins in desmosomes). Thus far, there has been no published study on QOL in Korean patients with pemphigus.ObjectiveTo study the impact of pemphigus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 20 publications
8
31
0
8
Order By: Relevance
“…Nonetheless, this difference did not reach statistical significance. This corroborates findings from three earlier studies examining HRQoL in patients with PV and PF using the SF‐36, DLQI and Skindex‐29 questionnaires . We also observed that patients with PV with mucocutaneous symptoms had the lowest EQ‐5D‐5L index scores, which highlights the importance of additional supportive treatments for patients with mucosal symptoms (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, this difference did not reach statistical significance. This corroborates findings from three earlier studies examining HRQoL in patients with PV and PF using the SF‐36, DLQI and Skindex‐29 questionnaires . We also observed that patients with PV with mucocutaneous symptoms had the lowest EQ‐5D‐5L index scores, which highlights the importance of additional supportive treatments for patients with mucosal symptoms (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…We acknowledge that there are several limitations of transferring value sets and EQ‐5D scores across different jurisdictions . Thirdly, in previous studies, the presence of antibodies against desmoglein 1 and 3 antigens was associated with disease activity and HRQoL in pemphigus . Our study was a cross‐sectional questionnaire survey; no serum samples were collected from patients that could have allowed us to measure antidesmoglein antibody levels.…”
Section: Discussionmentioning
confidence: 92%
“…Our results are in accordance with earlier studies assessing HRQoL and its predictors in patients with pemphigus by using EQ‐5D, SF‐36, WHOQOL‐BREF, DLQI and Skindex‐29 . Moreover, having a caregiver was associated with lower utilities for current health.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in accordance with earlier studies assessing HRQoL and its predictors in patients with pemphigus by using EQ-5D, SF-36, WHOQOL-BREF, DLQI and Skindex-29. 14,[40][41][42][43][44][45][46][47] Moreover, having a caregiver was associated with lower utilities for current health. Pemphigus may not only adversely affect HRQoL of patients but also places a burden on caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…For DLQI scoring, the dictum is higher the score, more is the impairment of QoL. Sung JY et al had analysed QoL in pemphigus patients and he found that DLQI score which was high during active disease was quite low during the disease remission phase because of treatment with steroids [18]. Using student's paired 't' test, it was also found that the mean difference between the two was highly significant (P value < 0.0001).…”
Section: Original Research Articlementioning
confidence: 99%